Uptake, depuration, dose estimation and effects in zebrafish exposed to Am-241 via dietary route. (October 2018) - Simon, O.; Barjhoux, I.; Camilleri, V.; Gagnaire, B.; Cavalié, I.; Orjollet, D.; Darriau, F.; Pereira, S.; Beaugelin-Seillers, K.; Adam-Guillermin, C.
Abstract: Zebrafish were chronically exposed to Am-241, an alpha-emitting radionuclide via daily consumption of an enriched artificial diet. Am-241 uptake was quantified in Danio rerio after 5 and 21 days of exposure via daily Am-spiked food ingestion and after 21 days of exposure followed by 5 days of depuration. Americium accumulates mostly in digestive tract, muscle, rest of the body but the accumulation levels and trophic transfer rate (0.033–0.013%) were low. Corresponding cumulative doses were calculated for the whole body (9 mGy) and for the digestive tract (42 mGy) with internal alpha radiation contributing to more than 99% of the total dose. Genotoxic effects (gamma-H2AX assay) and differential gene expressions of main biological functions were examined. Although fish were exposed to a low dose rate of 13 μGy h −1, DNA integrity and gene expression linked to oxidative stress, hormonal signaling and spermatogenesis were altered after 21 days of Am-241 exposure. These results underline the higher toxicity of alpha emitter Am-241, as compared to other studies on gamma radiation exposure. Highlights: Americium accumulates in muscle, rest of the body after trophic transfer in zebrafish. Despite the low dose rate close to 10 μGy h −1, molecular responses were observed. Differential gene responses in brain and genotoxic effect (γH2AX) were observed after Am-241 trophic contamination.